Losartan through Hsp70 Avoids Angiotensin II Induced Mesenchymal Epithelial Transition Proximal Tubule Cells from Spontaneously Hypertensive Rats - Costantino, Valeria Victoria (2019)
Renal injury related to hypertension is characterized by glomerular and tubulointerstitial damage. The overactivation of the renin-angiotensin system mainly by angiotensin II (AII) seems to be a main contributor to progressive renal fibrosis. Epithelial to mesenchymal transition (EMT) is a mechanism that promotes renal fibrosis. Owing to heat shock protein 70 (Hsp70) cytoprotective properties, the chaperone exhibits an important potential as a therapeutic target. We investigate the role of Hsp70 on Angiotensin II induced epithelial mesenchymal transition within the Losartan effect in proximal tubule cells (PTCs) from a genetic model of hypertension in rats (SHR). Methods: Primary cell culture of PTCs from SHR and Wistar Kyoto (WKY) rats were stimulated with AII, treated with Losartan (L), (L+AII) or untreated (Cc ). The functional Hsp70 role in Losartan effect, after silencing its expression by cell transfection, was determined by Immunofluorescence; Western blotting; Gelatin Zymography assays; Scratch wound assays; flow cytometry; and Live Cell Time-lapse microscopy. Results: (L) and (L+AII) treatments induced highly organized actin filaments and increased cortical actin in SHR PTCs. However, SHR PTCs (Cc ) and (AII) treated cells showed disorganized actin. After Hsp72 knockdown in SHR PTCs, (L) was unable to stabilize the actin cytoskeleton. We demonstrated that (L) and (L+AII) increased E-cadherin levels and decreased vinculin, α-SMA, vimentin, pERK, p38 and Smad2-3 activation compared to (AII) and (Cc ) SHR PTCs. Moreover, (L) inhibited MMP-2 and MMP-9 secretion, reduced migration and cellular displacement, stabilizing intercellular junctions. Notably, (L) treatment in shHsp72 knockdown SHR PTCs showed results similar to SHR PTCs (Cc ). Conclusion: Our results demonstrate that Losartan through Hsp70 inhibits the EMT induced by AII in proximal tubule cells derived from SHR.